Investigating the Dual-Action Potential of (Z)-6-methoxy 2-(naphthalen-1-ylmethylene) Benzofuran-3(2H)-one (AU-23): A Novel Synthetic Aurone Derivative with Antibacterial and Anti-Inflammatory Activ - Elsalami, Rabia Mrehil; Rullah, Kamal; Kassab, Yaman Walid; Qureshi, Mohammad Javed; Ahmad, Waqas; Mahadi, Mahani; Hassan, Masriana; Zin, Noraziah Mohamad; Kafo, Anwar Salm Kalifa; Yee, Chin Chai; Mohamad, Najwa (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim/Background Aurone is a well-known, naturally occurring, minor flavonoid with significant biological properties. However, their low abundance in nature limits their application in the medical field. In this study, we investigated the antimicrobial and anti-inflammatory properties of a novel synthetic aurone, (Z)-6-methoxy-2-(naphthalen-1-ylmethylene) benzofuran-3(2H)-one (AU-23). Materials and Methods AU-23 was synthesized via multistep synthesis reactions involving the oxidative cyclization of 2’-hydroxychalcones. AU-23 was tested for antibacterial, minimum inhibitory concentration and antibiofilm activity against several ATCC strains using agar well diffusion, broth-micro dilution and XTT assay methods respectively. Results At various concentrations, it selectively inhibited the growth of four strains (P. aeruginosa ATCC 9027, methicillin-resistant S. aureus (MRSA) ATCC 33591, methicillin-sensitive Staphylococcus aureus (MSSA) ATCC 25923 and methicillin-resistant S. aureus (MRSA) ATCC 43300). Moreover, it was observed that AU-23 had a bactericidal effect on sensitive strains of MSSA ATCC 25923 and P. aeruginosa ATCC 9027, as well as a bacteriostatic effect on MRSA ATCC 33591 and MRSA ATCC 43300. AU-23 also displayed effective antibiofilm activity against monomicrobial biofilms but not against polymicrobial biofilms. The findings of PCR study revealed that AU-23 downregulates the expression of pro-inflammatory cytokines and mediators (i.e., IL-6, IL-1β, iNOS and TNF-α), as well as crucial pattern recognition receptors (TLR4 and CD14) in LPS-stimulated RAW 264.7 cells. Molecular docking studies demonstrated that the ability of AU-23 to bind to the mouse TLR4/MD-2 complex was comparable to that of dexamethasone. Conclusion The results of several studies conducted, suggests that AU-23 has the potential to function as an effective dual-action agent with antimicrobial and anti-inflammatory properties.
Keywords: Aurone; Antimicrobial activity; Antibiofilm activity; Anti-inflammatory activity; Docking study.